Morandi's last prophecy and the end of Renaissance politics - Dooley, Brendan Maurice, 1953- (Princeton University Press, 2002)
"One year before Galileo's, another trial was the talk of Rome. The city's most notorious astrologer - Orazio Morandi, abbot of the monastery of Santa Prassede - was brought before the governor's court on charges of possessing prohibited books, fortune telling, and political chicanery. His most serious crime was to have predicted the death of Pope Urban VIII, the news of which spread as far as Spain, where cardinals quickly embarked for Italy to attend a conclave that would not occur for fourteen years. The pope, furious at such astrological and political effrontery, personally ordered the criminal inquiry that led to Morandi's arrest, trial, and death in prison, probably by assassination." "Based on new evidence, this book chronicles Morandi's fabulous rise and fall against the backdrop of enormous political and cultural turmoil that characterized Italy in the early seventeenth century. It documents a world in which occult knowledge commanded power, reveals widespread libertinism behind monastery walls, and illuminates the arduous metamorphosis of intellectual culture already underway. It also sets the stage for, and lends new understanding to, the trial of Galileo."--Jacket